Annular pancreas in neonate patients - Sarah Carvalho; Lucas Barreiros; Carlos Eduardo Binatti; Guilherme de Freitas Paganoti; Graziela de Araújo Costa; Viviane Mauro Corrêa Meyer (Medicina, 2022)
Objective: Reinforce that, despite being a rare condition, annular pancreas must be considered as a differential diagnosis for intestinal obstructions in the newborn period. Case description: This case report refers to a 13-days newborn admitted to the emergency room presenting with postprandial vomiting and progressive weight loss since maternity discharge. The patient did not respond to initial interventions that included IV antibiotics and insertion of a nasogastric tube. A contrasted study of the upper digestive tract (esophagus, stomach and duodenum) found a luminal narrowing on the second duodenal portion. The patient was submitted to an exploratory laparotomy which found a pancreatic-tissue ring involving the second part of the duodenum. Despite rare, we reinforce that annular pancreas must be considered as a differential diagnosis for intestinal obstructions in the newborn period. Comments: Annular pancreas is a rare congenital defect in which a ring of pancreatic tissue encircles the duodenum, causing different degrees of intestinal obstruction.